Surgical resectability of pancreatic adenocarcinoma: CTA - Wong, Jimmie C. (Springer-Verlag, 2009)
Imaging studies play an important role in the diagnosis and management of patients with pancreatic adenocarcinoma. Computed tomography (CT) is the most widely available and best validated modality for imaging these patients. Meticulous technique following a well-designed pancreas protocol is essential for maximizing the diagnostic efficacy of CT. After the diagnosis of pancreatic adenocarcinoma is made, the key to management is staging to determine resectability. In practice, staging often entails predicting the presence or absence of vascular invasion by tumor, for which several radiologic grading systems exist. With advances in surgical techniques, the definition of resectability is in evolution, and it is crucial that radiologists have an understanding of the implications of findings that are relevant to the determination of resectability.